1996
DOI: 10.1111/j.1365-2222.1996.tb00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a strong, positive association between atopy and the HLA class II alleles DR4 and DR7

Abstract: We observed that HLA-DR 4 and DR7 alleles are significantly implicated in their susceptibility to the disease and suggest that this susceptibility is more related to atopy than to specific responses to allergens. According to previous studies, we could also submit that in atopic patients with asthma, DR4 alleles at the least, could be more closely associated with atopy than with asthma per se. Conversely, we suggest that some allelic DQA1 and DQB1 sequences might confer protection against the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…We investigated genes of the MHC that encode molecules involved in immune response by presenting antigens for T cell recognition (21). We have previously reported an increase in the HLA class II alleles DR4 and DR7 in atopic and asthmatic patients (11). HLA-DR has also been found to be of prognostic significance in sarcoidosis, a systemic disease with prominent pulmonary involvement (22).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We investigated genes of the MHC that encode molecules involved in immune response by presenting antigens for T cell recognition (21). We have previously reported an increase in the HLA class II alleles DR4 and DR7 in atopic and asthmatic patients (11). HLA-DR has also been found to be of prognostic significance in sarcoidosis, a systemic disease with prominent pulmonary involvement (22).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, genes that mediate susceptibility to atopy may influence disease severity. An association between human leukocyte antigen (HLA) class II antigens and the IgE response has been reported (8) and we have previously found strong associations between some major histocompatibility complex (MHC) class II alleles (DR4-DR7) and allergic diseases (9)(10)(11). It has also been shown that HLA-DR was the only class II antigen expressed in nasal polyps of CF patients (12).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The human MHC on chromosome 6p, particularly HLA [113,114,115,116] and tumour necrosis factor (TNF) locus polymorphism [117,118], has also been extensively investigated, as has polymorphism in the 12q15-24 region [119,120]. SNPs in other candidate genes that have been investigated include, but are not limited to, the following: the α region of the T-cell receptor (TCR) α/δ locus [121], the α 1 -antitrypsin gene (α 1 -AT) [122,123,124], histo-blood-group genetic systems [125], the cystic fibrosis gene (ΔF508) [126,127], Gm allotypes of IgG genes [128], the Ig heavy chain γ 4 locus (IGHG4) [129], the Clara cell secretory protein (CC16) locus [130,131], the chemokine receptor loci on chromosome 3 [132,133], and the gene encoding angiotensin-converting enzyme (ACE) [134].…”
Section: Snps and Asthma Susceptibilitymentioning
confidence: 99%